Walden [videorecording (Blu-Ray)] - Davis, Mick, 1961-; Hirsch, Emile, 1985-; West, Shane; Garner, Kelli, 1984-; Coulter, Steve (Uncork'd Entertainment, 2022)
Walden Dean is a stenographer and being the ghost of the courtroom, his mind is agonizingly crammed witnessing the torrent of injustice, until now. Discovering he has a terminal illness sends him into a rage that has been simmering deep within him for years and now he is about to take justice into his own hands, in the most gruesome ways imaginable.